Erythema Multiforme and COVID-19: A Case Report and Deep Insight - Mustafa Mahmood Eid (Dubai Medical Journal)
There are several differences in illness presentation in clinical practice. Because diseases are ever-evolving, a single negative test cannot totally exclude the presence of a disease. The most frequent etiologies of erythema multiforme (EM), a prevalent mucocutaneous condition, are herpes infection and the use of numerous medicines. As a novel virus, SARS-CoV-2 is not often the primary differential for EM eruptions. This case represents a young female patient who presented solely with EM symptoms involving the distal parts of her upper and lower extremities after a positive swab for SARS-CoV-2. The condition improved with symptomatic treatment, and there were no major complications.